Business plan for opening a retail store focused on personal care products in Iceland - María Guðmundsdóttir 1995- (2021)
Before an entrepreneur establishes a business, it is important to do proper market research to see if there is a need or demand for the solution the business provides. If demand exists, the entrepreneur needs to set up a business plan. The business plan explains the main foundation of the idea and its risk factors. A good business plan can determine whether investors are willing to finance the business or not. Both financial institutions and individual venture capital investors demand a high-risk premium for investing in startups. In this thesis, the object is to present a complete business plan for a new business idea, based on research of the Icelandic market, and determine whether the idea is profitable and worth investing in. The goal of the thesis is to answer if it is profitable to open a new retailer in Iceland, focusing on known cosmetics brands offered at a lower price than currently is offered in the Icelandic market. The findings of the study point out that despite high operating costs, the project seems profitable. The findings show that there is high demand in the Icelandic market for known cosmetic products. By lowering the price to consumers, the gains from increase in sold volume would weigh heavier than the reduced margin of each unit sold. The thesis sets up the possibility to take the idea further and apply it to the market with support from investors Áður en stofnað er fyrirtæki á grundvelli viðskiptahugmyndar er nauðsynlegt að kanna hvort spurn sé eftir vörunni á markaðnum. Ef eftirspurnin er fyrir hendi er mögulegt að nauðsynlelgt að setja upp viðskiptaáætlun. Viðskiptaáætlun útskýrir helstu þætti hugmynd- arinnar og hvernig áhætta getur aukist eða minnkað eftir því hve vel gengur að selja vöruna eða þjónustuna. Viðskiptaáætlunin getur þess vegna skipt sköpum þegar kemur að því að ná í fjárfesta, bæði banka sem eru yfirleitt utanaðkomandi fjárfestar til lengri tíma með hærri ávöxunarkröfu eða áhættufjárfesta sem vilja einnig háa ávöxtunarkröfu og taka ...